Influence of Structural Parameters of Main Load Train of Asymmetric Hub Bearings on Friction Torque - Tang Yibo; Qiu Ming; Yang Chuanmeng; Wang Huijie (Jixie chuandong)
Aiming at the problem of energy consumption caused by the asymmetric hub bearing friction and in order to more accurately analyze the influence of structural parameters on the friction torque, an improved analysis model of friction torque of asymmetric hub bearing considering pretightening force is established and verified by experiments, by using the coordinate transformation method. Assuming that the structural parameters of the right row of asymmetric hub bearings remain unchanged, the influence of the structural parameters of the left row (main bearing row) on the bearing friction torque is studied. The results show that there is an optimal overturning moment to minimize the friction moment of asymmetric hub bearings. With the increase of center distance, when the overturning moment is less than the optimal overturning moment, the friction moment of asymmetric hub bearings increases, and when the overturning moment is greater than the optimal overturning moment, the friction torque of asymmetrical hub bearings decreases. The friction torque of asymmetrical hub bearings decreases when the curvature radius coefficient of left row groove and the number of steel balls of left row are appropriately increased. The friction torque of asymmetrical hub bearings increases when the diameter of the left row of pitch circle and the diameter of the left row of steel ball of asymmetrical hub bearings increase. When overturning moment M1 is equal to 30 000 N·mm, the influence weights of left row structural parameters of asymmetric hub bearings on friction torque are as follows: curvature radius coefficient of the left row groove is greater than the number of steel balls in the left row; the number of steel balls in the left row is greater than the diameter of the pitch circle in the left row; the diameter of the pitch circle in the left row is greater than the diameter of steel balls in left row; the diameter of steel balls in left row is greater than the center distance.